Contributing factors to e-learning anxiety among university students (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The current study aimed to reveal the most important factors that contribute to e-learning anxiety among university students, and the researchers used the descriptive survey method, and a scale prepared by them was used as a tool for the study, and it was applied electronically in the form of Google Drive on a random sample of students from three universities in Riyadh according to the variables (Type - academic group - college - university) reached (302) students, and the study reached a set of results, the most important of which are: the most contributing factors to e-learning anxiety are: Poor internet services in my residential area, and the fear of pressing an error icon that is not intended to be used during e-learning sessions, annoyance about not being able to express what I want during e-lectures, feeling bored and monotony during e-learning lectures,  feeling panicky at the mere thought of the possibility of the internet being interrupted during online exams, and fear that my academic performance will decline during e-learning sessions. The study also found that there were statistically significant differences at the level of significance (0.05) between the responses of the sample members according to the gender variable (male - female), in favor of males, and according to the band variable (first - fourth), in favor of first-year students, and according to the college variable ( Theoretical – applied practical), for the benefit of the applied practical colleges category,